"Sauna" Activation toward Intrinsic Lattice Deficiency in Carbon Nanotube Microspheres for High‐Energy and Long‐Lasting Lithium–Sulfur Batteries. Issue 26 (3rd May 2021) - Zhang, Yongguang; Li, Gaoran; Wang, Jiayi; Luo, Dan; Sun, Zhenghao; Zhao, Yan; Yu, Aiping; Wang, Xin; Chen, Zhongwei
Abstract: Lithium–sulfur (Li–S) battery technology offers one of the most promising replacement strategies for conventional lithium‐ion batteries, but for several serious obstacles remain, such as the notorious polysulfide shuttling and their sluggish reaction kinetics. In this work, it is demonstrated that these problems can be significantly ameliorated via intrinsic lattice defect engineering in carbon‐based sulfur host materials. Specifically, porous carbon nanotube microspheres (ePCNTM) are developed through a scalable spray drying method, followed by a critical water‐steam etching under high temperature. Such "sauna" activation constructs abundant intrinsic topological defects in the carbon lattice, endowing ePCNTM with enhanced sulfur adsorbability and catalytic activity in sulfur redox reactions. In addition, the interwoven and highly porous architecture renders favorable conductivity, homogeneous sulfur distribution, and massive host–guest interactive surfaces. As a result, the ePCNTM‐based sulfur electrodes achieve excellent cyclability with an ultralow capacity attenuation rate of 0.046% per cycle upon 500 cycles, excellent rate capability up to 3 C, and decent areal capacity retention of 3.2 mAh cm −2 after 50 cycles under raised high sulfur loading. Thus, this synergistic approach, combining composite nanostructuring and intrinsic defect engineering, yields highly competitive Li–S batteries, which is also expected to inform advanced material development in related energy fields. Abstract : Porous carbon nanotube microspheres are developed and following "sauna" activation are employed to construct abundant intrinsic topological defects in a carbon lattice. Strong chemical sulfur immobilization and catalyzed sulfur conversions are achieved based on the carbon‐defected sulfur host. The combination of nanostructuring and intrinsic defect engineering holds great promise in the development of high‐performance lithium–sulfur batteries.